NARRATIVE STRUCTURES ACROSS TELLINGS OF THE SAME â€œGOODâ€ TEACHING EXPERIENCE - Mambu, Joseph Ernest (Universitas Pendidikan Indonesia, 2013)
Abstract: This paper investigates narrative structures of the same story told three times by an advanced male EFL (i.e., English as a foreign language) learner. By narrative structures in this paper, I mean the sequence of narrative, especially in the light of the Labovian tradition of narrative analysis (Labov Waletzky, 1997; Labov, 1972; Wu, 1995), and how each narrative component (e.g., abstract, orientation, complicating action, result/resolution, evaluation, and coda) is fleshed out within and across tellings. Data analysis in this paper will attempt to answer the question of the extent to which these structures in one telling are similar or different across tellings of the same â€œgoodâ€ experiences (cf. Chafe, 1998; Polanyi, 1981; Prior, 2011). In Labovâ€™s (1972) data, â€œbadâ€ near-death experiences were elicited, and yet a â€œgoodâ€ result is conspicuous: death was overcome. Being asked to tell his â€œgoodâ€ story, the EFL learner concentrated on the favorable experience. This said, some hints at unfavorable experiencesâ€”typically filling in the complicating action slot, like in telling bad or embarrassing stories (as in Wu, 1995)â€”also emerged, which make analysis of â€œgoodâ€ experiences worthwhile in its own right. In particular, it can be hypothesized that the underlying structure of good experiences fits into the Labovian narrative structure with some nuanced variations across tellings. The findings support the hypothesis and suggest that repeated tellings of the same story provided the speaker in this study ample room to reflect on his past experience such that subsequent tellings can be more engaging than the first (or previous) telling.